Nematicity and structure in LaFe1-xCoxAsO - Wang, Liran; Sauerland, Sven; Klingeler, Rüdiger (Journal of magnetism and magnetic materials, 2019)
We present thermal expansion studies on single-crystalline LaFe1-xCoxAsO with doping levels of x = 0, 0.026, and 0.034, and on BaFe2As2. Anomalies in the thermal expansion coefficient α enable reading off the structural and magnetic transition temperatures TS and TN. The evolution of the orthorhombic distortion at TS is illustrated by length changes of the a- and b-axes and the experimentally determined orthorhombicity δ. The results are compared to BaFe2As2. Finally, the electronic phase diagram is discussed.
Gesehen am 03.06.2019
Im Titel ist "1-x" und "x" tiefgestellt